The Role of Investment Profitability, Actuarial Back up and Capital, on Financial Soundness: A Study on Indonesia General Insurance Industry - Arifatun Nasihah; Moch. Doddy Ariefianto (Budapest International Research and Critics University, 2022)
This study investigates the role of investment profitability, actuarial back up and capital, on financial soundness: a study on indonesia general insurance industry. We apply panel data econometric to a dataset comprised of 74 companies, annual frequency from 2006 to 2019; (General insurance companies have acquired 19 companies). We find that the results of this study indicate that investment profitability has a positive effect on financial soundness, actuarial back-up has a negative effect on financial soundness, capital has a negative effect on financial soundness. This study has important implications for business practices/regulations for the regulators of the Financial Services Authority. This research is expected to provide a reference for further research related to insurance.